2022
DOI: 10.3390/jcm11102737
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Studies in Gestational Diabetes Mellitus: A Systematic Review and Meta-Analysis

Abstract: Gestational Diabetes Mellitus (GDM) is the most common metabolic complication during pregnancy and is associated with serious maternal and fetal complications such as pre-eclampsia and stillbirth. Further, women with GDM have approximately 10 times higher risk of diabetes later in life. Children born to mothers with GDM also face a higher risk of childhood obesity and diabetes later in life. Early prediction/diagnosis of GDM leads to early interventions such as diet and lifestyle, which could mitigate the mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 108 publications
1
4
0
3
Order By: Relevance
“…C6, C7, C8B, C8G and C9 are the final complement components, essential in creating the membrane attack complex, which is the main effector of complement-mediated tissue damage [ 23 ]. Our data reveal that F12 is upregulated and confirms previous results [ 31 ]. Women with GDM have higher serum exosomal levels of F12 when compared to women with healthy pregnancies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…C6, C7, C8B, C8G and C9 are the final complement components, essential in creating the membrane attack complex, which is the main effector of complement-mediated tissue damage [ 23 ]. Our data reveal that F12 is upregulated and confirms previous results [ 31 ]. Women with GDM have higher serum exosomal levels of F12 when compared to women with healthy pregnancies.…”
Section: Discussionsupporting
confidence: 93%
“…In 2022, a systematic review and meta-analysis of biomarkers that are differentially expressed in women with and without GDM revealed that in GDM, C6, C7, C8B, C8G, C9 and C4BPA are downregulated [ 31 ]. It is important to note that this recent report mentioned that there are not case-control studies performed with sample collection from serum exosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Já para a prole dessas mulheres os riscos incluem macrossomia (20-30%), serem pequenos para a idade gestacional (7-10%), distocia de ombro, hipoglicemia neonatal, hiperbilirrubinemia neonatal, síndrome do desconforto respiratório até mesmo serem natimortos, e quando sobrevivem, possuem um risco maior de obesidade infantil e diabetes na vida adulta. Além disso, as mulheres com DMG têm dez vezes mais riscos de desenvolver diabetes mellitus tipo 2 ao longo da vida em até 10 anos após o parto (Sriboonvorakul et al, 2022).…”
Section: Resultsunclassified
“…A revisão sistemática e meta-análise produzida por Sriboonvorakul et al, (2022) é uma das mais abrangentes e atualizadas sobre biomarcadores (CB) para DMG. Este estudo identificou 22 CB altamente replicáveis que eram significativamente diferentes (9 CBs foram regulados positivamente e 12 CBs regulados negativamente) entre mulheres com DMG e as que eram controles em várias plataformas proteômicas, tipos de amostras, frações de sangue e tempo de coleta de sangue e continentes.…”
Section: Resultsunclassified
See 1 more Smart Citation